A református peregrináció kollektív és személyes emlékezete a kora újkorban - HEGYI, Ádám (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The Collective and Personal Memory of Reformed Peregrination in the Early Modern Period. In the Early Modern Period, Reformed students in Hungary created a complex network. This network helped them to organize their university studies abroad. The memory of the peregrination is documented in ego-documents and other records. The culture of memory was maintained by a complex network of personal and collective elements. The oral tradition played an important role in the system, as much information was preserved by word of mouth. Written sources of memory survive in student lists, friendship books, diaries, and church chronicles. However, traces of historical research that went beyond memory can be found not only in the works of scholars (Péter Bod, Miklós Sinai, István Weszprémi) but also in congregational documents.